2019
DOI: 10.1177/1045389x19873419
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear ultrasonic inspection of smart carbon fibre reinforced plastic composites with embedded piezoelectric lead zirconate titanate transducers for space applications

Abstract: Carbon fibre reinforced plastic composites used in spacecraft structures are susceptible to delamination, debonds and fibre cracking that may arise during manufacturing, assembly or in-service operations (e.g. caused by debris impacts in near-Earth orbital spaceflights). Therefore, in situ and real-time health monitoring is necessary to avoid time-consuming and unsafe visual inspections performed either on-ground or during extra vehicular activities. In this article, a recently created ‘smart’ carbon fibre rei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 60 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…Moreover, this choice is motivated by the existence of a similar integration in the literature: Andreades and al. study [9]. Their work consists of a PZT integration into laminated composite, on the same basis of components and condition of composite curing than this present study.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, this choice is motivated by the existence of a similar integration in the literature: Andreades and al. study [9]. Their work consists of a PZT integration into laminated composite, on the same basis of components and condition of composite curing than this present study.…”
Section: Introductionmentioning
confidence: 97%
“…To overcome such bonding layer issues under environmental conditions and also provide protection from impacts, one solution is the integration of the SHM system directly into the material. Composite materials allow the integration of a monitoring system directly into the material during manufacturing [18][19][20][21][22][23][24][25][26][27][28][29][30]. Moreover, as a co-cured surface-mounted SHM system, the manufacturing process of the composite material can be monitored directly from the beginning of the composite fabrication with an integrated SHM system [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…A few recent papers have shown the use of an embedded PZT in laminate CFRP for damage detection. Andreades et al [18] reported artificial delamination and real impact damage detection with a nonlinear ultrasonic method using an embedded PZT (6 mm diameter and 0.3 mm thick) in a CFRP laminate with GFRP galvanic insulation (0.1 mm thick). Huijer et al [29] embedded PZT in a CFRP to detect the onset of damages with the method of acoustic emission monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Such methods and the necessary tools are most in demand in manufacturing of load carrying structures, whose defects can cause emergencies or some dangerous failures. Among the known SHM and NDE methods of the polymeric composite materials the acoustic based methods are most effective and used in practice [1][2][3][4]. The common difficulties at the design of efficient acoustic based SHM of polymeric composites are the structural anisotropy of the elastic [2] and high damping properties [1,[5][6][7][8][9] of the materials that reduces the wave propagation distance [9,10].…”
Section: Introductionmentioning
confidence: 99%